Применение кинезотерапии в лечении дегенеративно-дистрофических расстройств - Жогина, О. А.; Сердюк, И. А.; Сушко, О. А. (ХНУРЕ, 2021)
The study involved 234 patients with degenerative-dystrophic disorders of the spinal column. Rehabilitation of vertebral pathology was carried out using the multifunctional hardware and software complex EN-TreeM. The assessment of the state of the neuromuscular apparatus was carried out using electromyography. After the course of rehabilitation, the patients showed a significant decrease in pain and inflammation up to the complete relief of pain syndrome and destructive inflammatory reactions, and increase in the range of motion.
Keywords: позвоночник; дегенеративно-дистрофические заболевания; нейрореабилитация; кинезотерапия